2021
DOI: 10.21203/rs.3.rs-191827/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ionomic and metabolic responses to drought stress in elite wheat seedlings under two phosphorus levels

Abstract: Background Wheat (Triticum aestivum L.) is the main food crop in the worldwide. Low soil phosphorus levels and drought conditions are important constraints for wheat production in most of the areas where wheat is grown. In this study, the analysis of mineral elements and metabolites were used to investigate the ionomic and metabolic responses to drought stress of wheat plants cultured by low phosphorus (LP) and conventional phosphorus (CP) supply, respectively. Results We found that the wheat plants subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Another multi-omics approach shed light on combined yieldrelated traits and enhanced abiotic stress tolerance in tobacco [277]. Recently, ionomics and metabolomics studies revealed the role of P in wheat plants in improving drought stress tolerance [278]. Based on their findings, T. aestivum plants in the low phosphorus (LP) treatment were more drought tolerant than those in the conventional phosphorus (CP) treatment, which is likely due to the presence of a comprehensive mobilization of sugar metabolism, that regulates osmotic balance, as well as the accumulation of various organic acids, or the regulation of intracellular ion homeostasis.…”
Section: Ionomics and Integrated Omics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another multi-omics approach shed light on combined yieldrelated traits and enhanced abiotic stress tolerance in tobacco [277]. Recently, ionomics and metabolomics studies revealed the role of P in wheat plants in improving drought stress tolerance [278]. Based on their findings, T. aestivum plants in the low phosphorus (LP) treatment were more drought tolerant than those in the conventional phosphorus (CP) treatment, which is likely due to the presence of a comprehensive mobilization of sugar metabolism, that regulates osmotic balance, as well as the accumulation of various organic acids, or the regulation of intracellular ion homeostasis.…”
Section: Ionomics and Integrated Omics Approachesmentioning
confidence: 99%
“…Interestingly, they also found the impact of different P supply on elements. Viz., K, Ca 2+ , P, Si, Na + , Mn, Mg, and Zn which were differently regulated in presence of LP and CP treated plants during drought stress [278]. Subsequently, a variety of omics techniques has been successfully employed to better understand the genetic processes that regulate the plant ionome [279].…”
Section: Ionomics and Integrated Omics Approachesmentioning
confidence: 99%